The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.cgh.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Definition, Pathogenesis, and Management of That Cursed Dyspepsia

Abstract: Dyspepsia is an umbrella term used to encompass a number of symptoms thought to originate from the upper gastrointestinal tract. These symptoms are relatively nonspecific; not surprisingly, therefore, a myriad of conditions may present with any one or a combination of these symptoms. Therein lays the clinician's first challenge: detecting the minority who may have a potentially life-threatening disorder, such as gastric cancer, from a population whose symptoms are, for the most part, considered functional in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 152 publications
0
31
0
4
Order By: Relevance
“…30 The symptoms during a GE study may be explained by abnormal GE, decreased gastric accommodation, and increased gastric sensitivity. 1 In this study, the symptoms during the GE study and during duodenal lipid infusion were correlated, which suggests that the small intestine may also contribute to symptoms during a GE study. We previously observed that 58% of dyspeptic patients had moderately severe or more intense symptoms during duodenal lipid infusion.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…30 The symptoms during a GE study may be explained by abnormal GE, decreased gastric accommodation, and increased gastric sensitivity. 1 In this study, the symptoms during the GE study and during duodenal lipid infusion were correlated, which suggests that the small intestine may also contribute to symptoms during a GE study. We previously observed that 58% of dyspeptic patients had moderately severe or more intense symptoms during duodenal lipid infusion.…”
Section: Discussionmentioning
confidence: 53%
“…32 Gastric accommodation and sensitivity were not assessed. 1 In summary, severe symptoms during the GE scintigraphy explained respectively 62% and 40% of the variance in daily symptom severity and QOL in NUD. The symptoms during a GE study may provide a biomarker of NUD.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations